Characterization of Natural Fiber Extracted from Sesbania rostrata: An Alternative Potential for Synthetic Fibers (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Enriching natural materials is essential for developing eco-friendly composites in structural and automotive applications. The aim of this work is to extensively characterize new natural cellulosic fiber extracted from Sesbania rostrata stem.       S. rostrata fibers (SRFs) show cellulose content of 64.36 % with a range of tensile strength from 156 to 460 MPa and have a low density of 1.365 g/cm3. SRFs has crystallinity index of 58.41%, which is comparable with that of other common natural fibers. Furthermore, SRFs can resist the degradation of cellulose up to 246°C, which is revealed by thermogravimetric analysis.